2016
DOI: 10.11138/mltj/2016.6.4.480
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of anterior cruciate ligament injury in football players: a systematic review of the literature

Abstract: SummaryBackground: The ACL lesion represents one of the most dramatic injuries in a sportsman's career. There are many injury risk factors related to intrinsic, or non-modifiable, and extrinsic, or modifiable, factors. In literature at today current evidence suggests that ACL injury risk is multifactorial and involves biomechanical, anatomical, hormonal and neuromuscular factors. Purpose: To perform a systematic review of the literature concerning the ACL injury risk factors in soccer. Conclusion:The injury ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
(17 reference statements)
0
15
0
Order By: Relevance
“…Previous Injury A history of previous injury continues to be the most consistent and strongest risk factor for future injury, and this also holds true for specific injuries [9,[25][26][27][28][29]. For example, a history of previous hamstring injury is associated with future hamstring injury among male players [25,28], previous ACL injury is associated with risk of future ACL injury [29], and previous ankle sprain injury is related to the emergence of new ankle sprain injuries [27].…”
Section: Risk and Protective Factors Non-modifiable Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous Injury A history of previous injury continues to be the most consistent and strongest risk factor for future injury, and this also holds true for specific injuries [9,[25][26][27][28][29]. For example, a history of previous hamstring injury is associated with future hamstring injury among male players [25,28], previous ACL injury is associated with risk of future ACL injury [29], and previous ankle sprain injury is related to the emergence of new ankle sprain injuries [27].…”
Section: Risk and Protective Factors Non-modifiable Risk Factorsmentioning
confidence: 99%
“…One systematic review suggested that increasing age was a risk factor for future hamstring injury among male players [25]. Another systematic review concluded that existing literature was insufficient to infer any relationship between age and the risk of ACL injury among soccer players [29]. In a single prospective study, age > 14 years was a significant risk factor for future acute knee injury among female players [30].…”
Section: Risk and Protective Factors Non-modifiable Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Difficulties in coping with these demands are related to increased injury risk. Among injuries, ruptures of the anterior cruciate ligament (ACL) are considered some of the most dramatic events that may affect players' careers (Volpi et al, 2016). Also, women are, in comparison to the men footballers, exposed to a two to three times higher risk of ACL injury (Waldén, Hägglund, Werner, & Ekstrand, 2011).…”
mentioning
confidence: 99%
“…Due to discouraging results of clinical studies from the 1970s and 1980s, primary repair of the anterior cruciate ligament (ACL) was more or less abandoned and replaced by surgical reconstruction with autograft or allograft material as the gold standard from the 1990s onwards [1][2][3][4][5] . The clinical results achieved by ACL reconstruction are generally accepted.…”
Section: Introductionmentioning
confidence: 99%